2021
DOI: 10.1007/s11998-021-00521-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of edge formation during the coating process of Li-ion battery electrodes

Abstract: In this manuscript, a method to reduce superelevations of lateral edges in cross-web direction during slot die coating of shear-thinning slurries for Li-ion battery electrodes (LIB) was developed. Therefore, the impact of the inner slot die geometry on the edge elevations was investigated. These elevations of the coating could be almost eliminated by optimizing the flow profile at the outlet of the slot die by modification of the internal geometry. This adaption is an essential step in optimizing the coating q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Elevated coating edges for example detrimentally affect downstream processes such as coil winding or calendering, leading to cracks in the electrode layer as well as deformation or tearing of the current collector (Figure 2d). [16] The coating step is followed by the drying of the electrode layer, typically using convective methods such as heated laminar air flows. This step, additionally to being a production bottleneck, is the most energy intensive step since significant quantities of solvents must be removed from the electrode while the structure is being formed.…”
Section: Electrode Manufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated coating edges for example detrimentally affect downstream processes such as coil winding or calendering, leading to cracks in the electrode layer as well as deformation or tearing of the current collector (Figure 2d). [16] The coating step is followed by the drying of the electrode layer, typically using convective methods such as heated laminar air flows. This step, additionally to being a production bottleneck, is the most energy intensive step since significant quantities of solvents must be removed from the electrode while the structure is being formed.…”
Section: Electrode Manufacturingmentioning
confidence: 99%
“…High precision is required to reach the desired electrode loading while ensuring a uniform coating geometry. Elevated coating edges for example detrimentally affect down‐stream processes such as coil winding or calendering, leading to cracks in the electrode layer as well as deformation or tearing of the current collector (Figure 2d) [16] …”
Section: Battery Electrode Manufacturing and Quality Assurancementioning
confidence: 99%
“…As already known in literature, the influence of the dimensionless gap G * mitigates the formation of edge elevations. [1,10,15] A decreasing dimensionless gap G * results in a decreasing draw ratio of coating speed and average flow velocity below the die lips. This counteracts the neck-in flow and surface tension mechanism in edge formation and leads to decreasing fluid flow inwards the center of the coating.…”
Section: Influence Of the Coating Gap On Edge Formationmentioning
confidence: 99%
“…In addition, experiments with different coating gaps can be compared using the known dimensionless coating gap G * from Reproduced with permission under the terms of the Creative Commons CC BY license. [1] Copyright 2021, the Authors. Published by Springer Nature.…”
Section: Introductionmentioning
confidence: 99%
“…Current research has shown that adjustments to the (inner) slot die geometry influence the formation of edge elevations. 13 This motivates the establishment of more advanced methods to investigate the complex interactions of the various influencing parameters, which have an effect on edge elevations. One way to meet these requirements is to implement a CFD-simulation model and deriving novel solution approaches.…”
Section: Introductionmentioning
confidence: 99%